Three-dimensional numerical modeling and characterization of two-stage and multilayer thermoelectric couples. Issue 7 (27th May 2016) - Zhou, Minfeng; He, Yongling; Chen, Yanmin
ABSTRACT: The two-stage thermoelectric couple (TE couple) and the multilayer TE couple are proposed and their output performance is compared with the conventional TE couple in this paper. Three dimensional (3-D) numerical and finite element models are established for these three types of TE couples which are analyzed in the ANSYS Workbench environment. Simulation results show that the output voltage and the current of the two newly designed TE couples increase in a certain extent than those of the conventional device before the load resistance reaches a critical value, however, the multilayer TE couple has the best performance. Similar conclusions can be drawn from the results of comparisons with the maximum output power and the maximum heat conversion efficiency between different types of TE couples. When thicknesses of the intermediate ceramic substrate and the intermediate copper conductor change, the output performance of the two newly-designed types of TE couples can be improved further. The maximum output power and the maximum heat conversion efficiency of the multilayer TE couple increase by 71.15% and 14.87%, respectively, when compared with those for the conventional device under certain conditions. Therefore, the multilayer TE couple has the potential to be one of the future development directions of TE couple structures.